2014
DOI: 10.1002/wsb.407
|View full text |Cite
|
Sign up to set email alerts
|

Modeling marbled murrelet (Brachyramphus marmoratus) habitat using LiDAR‐derived canopy data

Abstract: LiDAR (Light Detection And Ranging) is an emerging remote-sensing tool that can provide fine-scale data describing vertical complexity of vegetation relevant to species that are responsive to forest structure. We used LiDAR data to estimate occupancy probability for the federally threatened marbled murrelet (Brachyramphus marmoratus) in the Oregon Coast Range of the United States. Our goal was to address the need identified in the Recovery Plan for a more accurate estimate of the availability of nesting habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Future versions of the BC Model might therefore become more reliable as VRI is updated. Both VRI and the BC Model might be improved further with the application of new technologies, such as Light Detection and Ranging (LiDAR), which is currently being tested for identifying and mapping Marbled Murrelet forest habitat (Clyde 2017, Hagar et al 2014.…”
Section: Effects Of Spatial Sale Survey Intensity and The Source Of Datamentioning
confidence: 99%
“…Future versions of the BC Model might therefore become more reliable as VRI is updated. Both VRI and the BC Model might be improved further with the application of new technologies, such as Light Detection and Ranging (LiDAR), which is currently being tested for identifying and mapping Marbled Murrelet forest habitat (Clyde 2017, Hagar et al 2014.…”
Section: Effects Of Spatial Sale Survey Intensity and The Source Of Datamentioning
confidence: 99%
“…Predictors of basal area or dbh can be estimated by LiDAR, but we did not test any because of their allometric derivation from canopy heights. Habitat models derived from LiDAR provide significant advantages over existing models constructed from ground data or imputation techniques (Hagar et al 2014, Ackers et al 2015. Because LiDAR measures are continuous across the areas of acquisition, the LiDAR-derived habitat model can be used directly to estimate suitability throughout the entire area.…”
Section: Lidar Strengths and Weaknessesmentioning
confidence: 99%
“…Furthermore, multi‐scale analyses important to understanding habitat requirements are rarely performed with field data because data collection is laborious (Wiens , Scott et al , Seavy et al ). Although modeling with remotely sensed data can facilitate multi‐scale analyses and straightforward mapping of habitat suitability, the resolution and types of habitat information are sometimes too coarse for biologically meaningful analyses or local‐level planning (Ohmann and Gregory , Hagar et al , Ackers et al ).…”
mentioning
confidence: 99%
“…Airborne laser scanning captures a range of structural features important to the ecophysiological needs of birds, enabling ecologically relevant HSM for species such as the Northern Spotted Owl (Strix occidentalis caurina; Ackers et al 2015, Hagar et al 2020. Hagar et al (2014) demonstrated the feasibility of ALS informed HSM for murrelets, with canopy cover, tree height, structural complexity, and distance to the coast used as predictors in a binomial regression model that successfully discriminated murrelet occupancy among forest stands in Oregon. However, this model cannot be replicated in BC due to the lack of reliable absence data and latitudinal differences in forest composition and structure.…”
Section: Introductionmentioning
confidence: 99%